Effects of a free radical scavenger N-tert-butyl-alpha-phenylnitrone (PBN) on short-term recovery of immature rats after status epilepticus - Rejchrtová, J; Kubová, H; Druga, R; Mares, P; Folbergrová, J (Physiological research, 2005)
The present study examined the effects of a free radical scavenger, N-tert-butyl-alfa-phenylnitrone (PBN) on lithium-pilocarpine-induced status epilepticus (SE) and its short-term consequences in rats 12 (P12) or 25 (P25) days old. PBN (2 x 100 mg/kg i.p.) was injected according to the following schedules: 1) PBN-pretreated animals received the first dose 30 min prior to pilocarpine, the second dose was given 1 min after SE onset, and 2) PBN-treated animals received the first dose of PBN 1 min after SE onset and the second one 60 min later. Paraldehyde was administered to decrease mortality. Effects of PBN were highly age-dependent. In P25 group, PBN-pretreatment increased latency to SE onset and significantly suppressed the severity of motor manifestation of SE. Both PBN pretreatment and treatment improved recovery after SE. In contrast, administration of PBN in P12 animals did not affect SE pattern or recovery after SE. Administration of PBN had no effects on the motor performance of animals 3 and 6 days after SE. Neuronal damage was examined 24 h and 7 days after SE using Fluoro-Jade B staining. Mild neuroprotective effects of PBN in hippocampal fields CA1 and CA3 occurred in P25 rats in both experimental schedules. In contrast, administration of PBN aggravated neuronal injury in the hippocampus in P12 rats. Administration of PBN to intact rats did not induce neurodegeneration in either age group.
Keywords: Recovery of Function; Male; Rats, Wistar; obnova funkce; Cyclic N-Oxides; Age Factors; mužské pohlaví; potkani Wistar; cyklické N-oxidy; status epilepticus; krysa rodu Rattus; Time Factors; Animals; Status Epilepticus; zvířata; Rats; časové faktory; Free Radical Scavengers; věkové faktory; oxidy dusíku; Nitrogen Oxides; scavengery volných radikálů